Antara Eksklusif dan Pluralis: Rekonstruksi Narasi Kekristenan atas Agama Leluhur - Vikry Reinaldo Paais (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2022)
The relationship between Christianity and indigenous religion has been going on for a long time, but this relationship is not placed in the discourse of inter-religious relations. This is related to the paradigm and social construction in Christianity which has not fully recognized the indigenous religion as a "religion". By using Paul Knitter's approach to the model of inter-religious dialogue, namely exclusivism, inclusivism, and pluralism, this paper aims to observe and analyze Christian narratives and paradigms on the existence of indigenous religion. The narratives and paradigm will be divided into two parts: exclusivism, and pluralism. On the one hand, In exclusivism, indigenous religion is considered as "animism" and not yet "religious", therefore it needs to be "religiousized", or more specifically "Christianized". On the other hand, pluralism focuses on plurality, equality, and emphasizes inter-subjectivity. The analytical method used is descriptive qualitative, which consists of data reduction, data analysis, and drawing conclusions. The data in this paper are sourced from: first, the results of observations made at the Jemaat GPM Siahari, and the Mausuane tribe settlement, Seram Utara Timur Kobi District, Central Maluku Regency. Second, interviews were conducted with several young Christian generations on the Ambon island. And third, literature. In the end, the results of this study indicate that exclusive narratives of Indigenous religion (Jesus is the only way of salvation and truth, the great commission of Jesus Christ, and ancestral religions are considered to have no religion and do not have a God) still tend to be dominant in the socio-religious scope than pluralist narratives (freedom, and religious pluralism).